Laterally π-Extensed Nitrogen-Doped Molecular Nanographenes – From Anti-Kasha Emission to Ping-Pong Energy Transfer Events - Beneventi, Giovanni Mariano; Schöll, Kilian; Platzer, Benedikt; Krug, Marcel; Mai, Lukas; Negri, Fabrizia; Cadranel, Alejandro; Jux, Norbert; Guldi, Dirk Michael (Advanced Energy Materials, 2024)
Nanographenes, which feature at least one dimension smaller than 100 nm, are drawing interdisciplinary attention. Understanding the interplay between structure and properties is, however, still in its infancy. Molecular nanographenes are much better suited to fill this knowledge gap than graphene quantum dots or nanoribbons. Their bottom-up synthesis allows atomic precision and, thereby, assists in handling structure and connecting it with properties. Herein, the effects of nitrogen-doping and lateral π-extension in molecular nanographenes and in their coordination complexes with ruthenium porphyrins are investigated. The presence of just nitrogen resulted in an increase of the fluorescence quantum yield, without, however, affecting the energy levels. Lateral π-extension of the nanographenes, instead, resulted in a modulation of the excited states energy, which leads to a thermally-activated dual fluorescence with quantum yields as high as 61%. In the corresponding coordination complexes, lateral π-extension resulted in a ping-pong energy transfer cascade, that is, from the nanographene to the metalloporphyrin and back to the nanographene. The results help to directly rationalize properties observed in both graphene quantum dots and nanoribbons. Moreover, they prove that molecular nanographenes are appealing components for solar energy conversion schemes, where the modulation of inter-component energy transfer is of utmost importance.
CRIS-Team Scopus Importer:2024-06-21
Keywords: anti-Kasha emission; coordination complexes; energy transfer; metalloporphyrin; molecular nanographenes